Blockchain-Based Security Mechanisms for MANETs: A Review of Performance and Challenges - Khalladi, Rachid; Fekir, Youcef; Rebbah, Mohammed (Informatica, 2025)
Mobile ad hoc networks MANETs are networks composed of a finite set of nodes that connect to each other by self-organizing using wireless connections without a fixed infrastructure. These characteristics make this type of networks more vulnerable to different types of attacks. In 2008, a new technology appeared called Blockchain. In recent years, this technology has become widespread as a means of implementing security in different applications. In addition, blockchain technology is introduced to overcome the vulnerabilities caused by the characteristics of MANETs, including the absence of a center of trust (Absence of a fixed infrastructure). To improve the security features, many blockchain-based security approaches are proposed for MANETs. The review delves into 16 recent blockchain-oriented security mechanisms, considering that blockchains can improve MANETs security (from 2019 to 2024). Our inclusion criteria were defined as technical relevance, MANET focus, and experimental validation. Performance was evaluated in terms of latency, scalability, energy consumption, and security effectiveness. A comparison was made to find examples of common themes, strengths, and outstanding issues. Our findings confirmed that although blockchain enhances data integrity, node authentication, and trust relationships, it causes computational overhead and latency. This paper emphasizes the trade-offs and outlines future research to optimize security benefits versus resource limitations in MANETs.